PERTUMBUHAN TANAMAN SAWI HIJAU (Brassica rapa var. parachinensis) AKIBAT PERLAKUAN LOGAM BERAT KADMIUM (Cd) - Masnur Turnip, Mila Mahfudiawati, Elvi Rusmiyanto P.W, (Jurnal Protobiont, 2016)
The use of chemical fertilizers and pesticides in agriculture in a continuous and excessive manner can cause damage to the soil, one of which is the increase of the cadmium (Cd) content. The increased level of Cd will have an effect on plant growth. This research aims to find out the growth of mustard greens due to the treatment of heavy metal (Cd) and to determine the concentration of Cd absorbed by plants. The research was carried out from March to May 2015 in the Biology Laboratory of the Faculty of Matematics and Naturan Sciences, of Tanjungpura University Pontianak, and the Cd analysis was conducted in the Laboratory of Agricultural Product Technology of the Faculty of Agriculture of Tanjungpura University. The eksperimental design used was the Completely Randomized Design (CRD) which consisted of 4 treatments and 3 repetitions, i.e. 0 ppm, 50 ppm, 100 ppm and 150 ppm. Research findings showed that the addition of cadmium reduces the number of leaves, leaf area, fresh weight, dry weight and chlorophyllcontent in the plant. The higher the concentration of Cd given to the plant, the higher the concentration of Cd absorbed by green cabbage.The highest concentration of Cd absorbed by green cabbage was 0,220 ppm at a treatment concentration of 150 ppm.